A Modified of Mixed Strategy Algorithm for Power Allocation on D2D Underlay Communication - Rahma, Nur; Suparta, I; Adriansyah, Nachwan; Prabowo, Vinsensius (Telkom University, 2022)
As time passes by, the need for telecommunication services will increase along with increasement of human’s population. To anticipate the flooding requests of telecommunication services, one of the solutions offered is by implementing D2D communication, especially in 5G architecture. In D2D 5G, focusing on underlay communication D2D uses the same frequency spectrum, so that opportunity of interference may happen, but the value of spectral efficiency (SE) may increase as a result of the effectiveness of the spectral that occurs. In terms of financing and its development, underlay D2D communication is considered more profitable for service providers. Based on this point, the authors propose a novel algorithm of modified mixed strategy algorithm for power allocation to make the power transmission cost be more effective. After the experiment conducted, the result shows that modified mixed strategy outperform baseline model which uses no power allocation algorithm.